2010
DOI: 10.1111/j.1540-6210.2010.02161.x
|View full text |Cite
|
Sign up to set email alerts
|

Public–Private Partnerships and the Public Accountability Question

Abstract: Public–private partnerships (PPPs) are growing in popularity as a governing model for delivery of public goods and services. PPPs have existed since the Roman Empire, but their expansion into traditional public projects today raises serious questions about public accountability. This article examines public accountability and its application to government and private firms involved in PPPs. An analytical framework is proposed for assessing the extent to which PPPs provide (or will provide) goods and services c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
244
0
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(257 citation statements)
references
References 23 publications
3
244
0
10
Order By: Relevance
“…Access comes in the form of financial, managerial, and technical expertise. This desire to access the private sector is based in the belief that the public sector is incapable on its own to accomplish the level of desired project efficiency (Forrer, Kee, Newcomer, & Boyer, 2010). Thus, the public agency desires an arrangement to account for known shortcomings, and those are believed to be correctable through the partnering with private business.…”
Section: Rationales For Public-private Partnershipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Access comes in the form of financial, managerial, and technical expertise. This desire to access the private sector is based in the belief that the public sector is incapable on its own to accomplish the level of desired project efficiency (Forrer, Kee, Newcomer, & Boyer, 2010). Thus, the public agency desires an arrangement to account for known shortcomings, and those are believed to be correctable through the partnering with private business.…”
Section: Rationales For Public-private Partnershipsmentioning
confidence: 99%
“…Other potential benefits include reducing the cost of contracting (Forrer et al, 2010), financial improvements on borrowing rates (Hodge & Greve, 2010), relationship-building due to the longterm nature of the contract (Brinkerhoff & Brinkerhoff, 2011;Steyer & Gilbert, 2013), and the perception of governmental innovation (Forrer et al, 2010;Link & Link, 2009). These represent financial-and perception-based benefits that aim to cut short-and long-term costs through the collaboration with private business partners and through the use of entrepreneurial financing strategies.…”
Section: Rationales For Public-private Partnershipsmentioning
confidence: 99%
“…The results show that because of the regional disparities in anthropogenic impact on the environment, formulating specific region-oriented energy saving and emission reduction strategies may provide a more practical and effective approach to achieving sustainable development in China. Xing et al [23] determined the influence of backwash effects and spread effects in Changsha, Zhujiang River, and Xiangtan in China, while Forrer et al [24] found that the key cities of China have exerted a backwash effect on the nearby rural counties and villages and a spread effect on other cities. Unfortunately, these geographical methods have not been widely applied to the study of sustainable development.…”
Section: Relationship Between Urban Pollution and The Regional Enviromentioning
confidence: 99%
“…A comprehensive framework is needed in order to allow policy makers to take stock of the state of the practice and appraise the costs and benefits of different instruments to take more informed decisions regarding the most appropriate instruments to be introduced. A PPP can generate positive benefits for government authorities when risks allocated between the public and the private sectors are balanced (Forrer et al 2010). On the contrary, if the risks transferred to the private counterparty are limited or inappropriate, the probability of adverse selection (Vecchi et al 2016;Saussier 2013) and moral hazard (Engel, Fischer, and Galetovic 2009;Hellowell, Vecchi, and Caselli 2015) increases, which may give rise to deleterious consequences (a forced renegotiation of the contract, bailout of the private operator or even a termination of the contract are examples).…”
Section: Introductionmentioning
confidence: 99%